Synthesis of water-soluble chitosan inhibitor from shrimp shells and its corrosion rate on mild steel in acidic solution - Nur Layli Amanah; Ika Dyah Widharyanti; Agung Nugroho (Universitas Sebelas Maret, 2021)
Synthesis of WSCI (Water Soluble Chitosan Inhibitor) from shrimp shell waste is carried out through demineralization, deproteination, and deacetylation processes. WSCI is obtained from monomer termination and H2O2 assistance. WSCI was characterized using Fourier Transform Infrared Spectroscopy (FTIR) and the degree of deacetylation was determined using the baseline method. The effect of adding WSCI to low carbon steel SS400 with a 1 M HCl corrosive environment was studied using the weight loss method at various concentrations and temperatures. The overall results of the research show that WSCI synthesis used in the prevention of corrosion have an inhibition efficiency of up to 74.6% at a concentration of 200 ppm at a temperature of 28oC. Inhibition efficiency and corrosion rate are known to increase with increasing WSCI concentration and corrosion rate decreasing with increasing temperature.